The Efficacy of Reap (Read-Encode-Annotate-Ponder) Toward Teaching of Reading Viewed from Students’ Self-Esteem - Yuli Nur Ariyani (IJIP : Indonesian Journal of Islamic Psychology, 2021)
Abstract This study aims at determining: (1) Read-Encode-Annotate-Ponder (REAP) is more effective than Direct Instruction in teaching reading; (2) students with high self-esteem have better reading skills than students with low self-esteem; (3) there is an interaction between teaching methods and self-esteem in teaching reading. This experimental research was carried out at MAN 1 Salatiga. The population was the tenth-grade students. The sample used cluster random sampling. Two classes were sampled: X.7 the experimental class was taught by REAP and X.9 the control class was taught by Direct Instruction. The research data used questionnaire and reading test. After testing for normality and homogeneity, the hypothesis is tested. Reading test results data were analyzed using 2 x 2 multifactor analysis of variance and Tukey's test. Based on data analysis, conclusions are drawn: (1) REAP is more effective than Direct Instruction for teaching reading; (2) Students with high self-esteem have better reading skills than students with low self-esteem; (3) There is an interaction between teaching methods and students' self-esteem to teach reading.AbstrakPenelitian bertujuan untuk mengetahui: (1) Read-Encode-Annotate-Ponder (REAP) lebih efektif daripada Direct Instruction dalam pengajaran membaca; (2) siswa dengan harga diri tinggi memiliki keterampilan membaca lebih baik daripada siswa dengan harga diri rendah; (3) ada interaksi antara metode pengajaran dan harga diri dalam pengajaran membaca. Penelitian eksperimen ini dilaksanakan di MAN 1 Salatiga. Dengan populasi siswa kelas X. Sampel menggunakan cluster random sampling. Dua kelas dijadikan sampel: X.7 kelas eksperimen diajar dengan REAP dan X.9 kelas kontrol diajar dengan Direct Instruction. Data penelitian menggunakan angket dan tes membaca. Setelah dilakukan uji normalitas dan homogenitas, maka dilakukan uji hipotesis. Data hasil tes membaca dianalisis menggunakan analisis varians multifaktor 2x2 dan uji Tukey. Berdasarkan analisis data, ditarik simpulan: (1) REAP lebih efektif daripada Direct Instruction untuk pengajaran membaca; (2) Siswa dengan harga diri tinggi memiliki keterampilan membaca yang lebih baik daripada siswa dengan harga diri rendah; (3) Ada interaksi antara metode pengajaran dan harga diri siswa untuk mengajar membaca.